Understanding the Diversity of Pharmacotherapeutic Management of ADHD With Co-occurring Autism: An Australian Cross-Sectional Survey - Mellahn, Olivia J.; Knott, Rachael; Tiego, Jeggan; Kallady, Kathryn; Williams, Katrina; Bellgrove, Mark A.; Johnson, Beth P. (Frontiers in Psychiatry, 2022)
Objectives Attention deficit hyperactivity disorder (ADHD) is frequently comorbid with other neurodevelopmental conditions, such as autism spectrum disorder (ASD), which can make clinical decision making around symptom management challenging for clinicians. There is a paucity of research examining pharmacotherapeutic management of children who have ADHD with comorbidities. We examined the range of medications used among children with ADHD and comorbid conditions. We reported on the comorbidities, symptom profiles and medication use among children with ADHD, ASD, or comorbid ADHD+ASD. Methods and Materials Caregivers of 505 children (2-18 years) with ADHD (n=239), comorbid ADHD+ASD (n=149), and ASD (n=117) completed a questionnaire on current medication use and clinical rating scales about their child’s symptoms, as part of a broader project investigating diagnosis and management of symptoms in children with ADHD and ASD. Results The parents of the ADHD group reported the highest rate of learning disorders (17.15%) and speech and language disorders (4.60%), while parents of the ADHD+ASD group reported higher rates of intellectual disability (5.37%), oppositional defiant disorder (20.13%), anxiety (38.93%), depression (6.71%) and genetic disorders (3.36%) in their children. ADHD was associated with the highest rate of psychotropic medication use (90%), followed by ADHD+ASD (86%) and ASD (39%). The parents of children with ADHD+ASD reported the highest rate of non-stimulant ADHD medication (25.5%), antipsychotic (18.79%), antidepressant (22.15%) and melatonin (31.54%) use by their children. Conclusions Children with comorbid ADHD+ASD diagnoses had higher rates of medication use, despite children with ADHD being more likely to take medication, likely due to the parents of children with ADHD+ASD reporting higher rates of other comorbid disorders. This research highlights that children with ADHD+ASD experience greater symptom severity and complexity and that targeted research is required with this group to optimise therapeutic outcomes and access to a range of interventions.